Nationalism in the Poetry of Dr. Allama Muhammad Iqbal and Walt Whitman: A Comparative Literary Analysis of I Hear America Singing and Tarana-I-Hindi - Aamir Sohail; Muhammad Zawar Khan (Scope : Journal of English Language Teaching, 2021)
This paper is based on the comparative study of the two poets, Allama Muhammad Iqbal from Pakistan and Walt Whitman from America as nationalistic poets of their specific age. Nationalism was a common theme in most of their works. These two poets belonged to different geographical social cultural and religious backgrounds but they have some similarities as well as differences. Allama Muhammad Iqbal was famous for the fan Islamist and he was considered as the Muslim nationalist of their time throughout the world while Walt Whitman was famous for American nationalism and democracy. All the time he speaks about the superiority of the American I have used the variation theory of comparative literature presented by changing Cao for the purpose to compare and contrast the work of two different for similarity as well as difference and another framework I will use comparative cultural studies presented by Totsy Zepetnek in my research.